Media Pembelajaran Berbasis Webtoon Untuk Menafsirkan Pandangan Pengarang Dalam Novel - Suciati Suciati; Sumarti Sumarti; Iing Sunarti (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2018)
This study was the development of webtoon-based literary learning media. The purpose of this study was to produce media, to test the feasibility of the media, and test the effectiveness of webtoon-based literary learning media to interpret the author's views in the novel Maafkan Aku, Kuala Mesuji written by Fajar for senior high school students. This study used the Research and Development (R D) method referring to the Borg and Gall model. The results of this study were (1) webtoon-based learning media entitled "Practical Tips for Interpreting the Viewer's Angle through the Webtoon", (2) webtoon was siotable to be used as learning media worthy of use as learning media to interpret the author's views according to the results of validation tests from experts, teachers , and peseta students, (3) the webtoon media proved to be effective in increasing students' learning abilities with the acquisition of an average value of pre test 65 and post test 88 with an average effectiveness of 0.71 with a high category.Penelitian ini ialah pengembangan media pembelajaran sastra berbasis webtoon, tujuan penelitian ini untuk menghasilkan media, menguji kelayakan media, dan menguji efektivitas media pembelajaran sastra berbasis webtoon untuk menafsirkan pandangan pengarang dalam novel Maafkan Aku, Kuala Mesuji Karya Fajar untuk siswa SMA kelas XII. Penelitian ini menggunakan metode Research and Development (R D) mengacu pada model Borg and Gall. Hasil penelitian ini berupa (1) media pembelajaran berbasis webtoon dengan judul ”Kiat Praktis Menafsir Sudut Pandang Pengarang Melalui Webtoon”, (2) media webtoon layak digunakan sebagai media pembelajaran menafsir pandangan pengarang sesuai dengan hasil uji validasi dari para ahli, guru, maupun peseta didik, (3) media webtoon terbukti efektif meningkatkan kemampuan belajar siswa dengan perolehan nilai rata-rata pre test 65 dan post test 88 dengan efektivitas rata-rata 0,71 dengan kategori tinggi.Kata Kunci: media, webtoon, pandangan pengarang.